2013
DOI: 10.4103/0974-8520.123110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on the effect of decoction of Pavetta indica Linn. in treatment of Purishaja Krimi with special reference to Enterobius vermicularis infestation

Abstract: Pavetta indica Linn. (Family: Rubiaceae; Sanskrit name: Papata) is 2-5 m tall, shrub or small tree with opposite branches and grows in the Asia - Pacific region including Sri Lanka. Purishaja Krimi is one of the worm infestations described in Ayurveda. Enterobius vermicularis is among the most common of worms affecting children and adults. E. vermicularis is considered as one type of Purishaja Krimi. Sri Lankan traditional and ayurvedic physicians use P. indica to treat different ailments including Purishaja K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In Malaysia, leaves are used to cure wounds and taken as a sedative while traditional and Ayurvedic physicians in Sri Lanka employ L. zeylanica in the treatment of worm infections successfully. However, the effect it has as an anthelmintic has still not been scientifically proven (Ediriweera, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Malaysia, leaves are used to cure wounds and taken as a sedative while traditional and Ayurvedic physicians in Sri Lanka employ L. zeylanica in the treatment of worm infections successfully. However, the effect it has as an anthelmintic has still not been scientifically proven (Ediriweera, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the limitation of the chemical drugs present on the market, a new approach is expected to be employed where natural medicinal plants are used as a treatment for this parasitic infection. On that account, the research was conducted to study the anthelminthic activity of L. zeylanica at different extraction solvents and concentrations in eluting worms based on the traditional Ayurvedic practice of this plant (Ediriweera, 2014). The success in proving its efficacy as an alternative treatment would be a stepping stone towards advancement in the development of a novel herbal medicinal plantbased product in the medical industry for helminthiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the leaves of the plant are consumed as a vegetable [2]. The extracts prepared from L. zeylanica exhibited hepatoprotective effects [3] and were found to be highly effective against Enterobius vermicularis infections in adults [4]. Furthermore, the lipophilic extracts have displayed potent anti-inflammatory activities by inhibiting the two enzymes; 5-lipoxygenase and microsomal prostaglandin E 2 synthase-1 involved in the synthesis of pro-inflammatory eicosanoids.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that Sri Lankan traditional and ayurvedic specialists use Pavetta indica Linn to relieve different ailments, including Purishaja Krimi (E. vermicularis) infestations successfully. [6].…”
Section: Introductionmentioning
confidence: 99%